A new approach to journal ranking: social structure in hospitality and tourism journals. Issue 2 (14th September 2018) - Koseoglu, Mehmet Ali
Abstract : Purpose: This study introduces a new approach, called the social structure approach, for ranking academic journals by focusing on hospitality and tourism journals; and a hybrid metric, including the combination of the journal impact factor via citations and a social network metric, called the journal knowledge domain index (JKDI). Design/methodology/approach: Twenty-five hospitality and tourism journals were selected to test this approach. Collaboration-based metrics, productivity-based metrics, and network-based metrics are considered components of the social structure approach. Additionally, a hybrid metric, including the combination of the journal impact factor via citations and a social network metric, JKDI, is developed. Findings: The study's findings show that top or leading journals have a weaker position in some social structure approach metrics compared to other (or follower) journals. However, according to the JKDI, leading journals have remained constant with the other ranking studies. Practical implications: The ranking of academic journals is vital for the stakeholders of academia. Consequently, the findings of this study may help stakeholders to design an optimal ranking system and formulate and implement effective research strategies for knowledge creation and dissemination. Originality/value: As one of the first in the journal-ranking literature, this study has significant implications, as it introduces a new ranking approach.